HUBUNGAN ANTARA PERSEPSI SISWA TENTANG PENILAIAN GURU DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR GEOGRAFI SMAN 5 PADANG - afryansih, nila (Jurnal Curricula, 2016)
This article aimed to obtain information, analyze and discuss data on the Relationship Between Students' perceptions of teacher assessment and Motivation to Learn Geography SMAN 5 Results Padang. The research method used was a survey method, type of correlational research study population was all class XI IPS is comprised of local, amounting to 4 162 people. The samples were taken with a proportional random sampling technique, where for each class taken at random with a proportion of 50% so that the sample was 81 students. The results: (1) Students' perceptions of teacher assessment is mostly good (45.68%). Results of hypothesis testing there is a positive relationship between students' perceptions of teacher assessment to student learning outcomes geography class XI IPS SMA N 5 Padang, including low power and small contributions made including, (2) motivation most students of class XI IPS SMAN 5 Padang generally poor (39.5%). Results of this study indicate there is a relationship between motivation and learning outcomes geography class XI IPS SMA N 5 Padang, the power relationship between motivation and learning outcomes geography including moderate and included a small contribution and (3) there is a positive relationship between students' perceptions of teacher assessment and motivation to the learning outcomes of students in class XI IPS SMA N 5 Padang, by the strength of the relationship between the two variables on the variable Y includes medium and small contributions made including. Motivation is the most dominant variables on learning outcomes as compared to the variable geography student perceptions of teacher assessment.